A critical discussion of inclusive approaches to sexualities in ELT. (19th April 2021) - Bollas, Angelos
Abstract: The aim of this article is to challenge heteronormative as well as homonormative practices in English language teaching. In doing so, the paper demonstrates that both complete absence of LGBTQI+ references in ELT materials, as well as recent attempts to provide more inclusive approaches to materials design and classroom practices, can be problematic for L2 learners irrespective of their sexuality. The paper traces current developments in ELT materials design with regards to inclusive classroom practices and argues that attempts towards exclusivity may reflect (hetero/homo)normative views, and can therefore perpetuate a culture—learning and otherwise—of discrimination and social exclusion. It concludes by identifying the need for an alternative approach—one that does not focus on inclusion but on diversity.